FAKTOR-FAKTOR YANG BERHUBUNGAN PEMBERANTASAN SARANG NYAMUK (PSN) DENGAN KEJADIAN DBD DI WILAYAH PUSKESMAS SELINDUNG (JURNAL SMART ANKES, 2021)
Dengue Hemorrhagic Fever (DHF) is a contagious disease caused by the dengue virus, transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. Based on the 5-year cycle, it can be seen an increase in dengue fever every year and in the five-year cycle. The number of dengue cases reported by the World Health Organization (WHO) can be seen in the first few decades of 2015-2018 as many as 1.3 million cases, increasing to 5.4 million cases in 2019. The purpose of this study is to determine the factors involved related to the eradication of mosquito nests (psn) with the incidence of dengue fever in the Puskesmas Selindung area of ​​2020. This study used an analytical survey with a case control method. The subjects of this study were a group affected by certain diseases or effects. In this case, the case sample is all dengue suspects registered and registered in the working area of ​​the Selindung Puskesmas from January to December 2019 with a total of 34 cases. Control is a group that is not affected by the disease or without effects. In this case, the control sample is the neighbor of the dengue sufferer who is not infected by DHF. In this study, the case sampling technique was carried out by total sampling. While sampling for control using accidental sampling was carried out by taking cases or respondents who happened to be present or available and were close to the case house (DHF sufferers). The results of this study indicate that the factors associated with the eradication of mosquito nests (psn) with the incidence of dengue fever in the Gerunggang Community Health Center in 2020 are knowledge p = 0.001, action p = 0.029, availability of information p = 0.004, support from health workers p = 0.014, support health cadres p = 0.028, while the dominant factor is knowledge (POR = 7.071).